Desain Sistem Penjadwalan Tenaga Keperawatan Rumah Sakit Menggunakan Algoritma Priority Scheduling - Mardzuki, Tati Harihayati; Lubis, Riani; Abdulloh , Mahfudz (Program Studi Teknik Informatika - Universitas Komputer Indonesia (UNIKOM), 2025)
Scheduling nursing staff in a hospital is a process that must be carried out every period to meet patient needs based on their services. The nursing staff scheduled in this study were nursing staff in the Outpatient Unit. The current schedule does not take into account the limitations of each nursing staff, such as nurses who are in advanced studies, pregnant, or are currently working as doctor's assistants. This has caused several complaints from several nurses, such as nurses whose pregnancy age is approaching 7-8 months getting an afternoon shift schedule more than four (4) times a month, which means it is not in accordance with the outpatient unit policy. The purpose of this study is to produce a scheduling system model by considering the limitations of nursing staff in the Outpatient Unit in the next period. The algorithm used in creating the nursing staff schedule is the priority scheduling algorithm, where this algorithm has been proven effective in managing the priority of the process sequence and has been applied to other information systems with satisfactory results. The results of the study indicate that the scheduling system model created can meet the needs of nursing staff in the Outpatient Unit